Catechol siderophores framed on 2,3-dihydroxybenzoyl-L-serine from Streptomyces varsoviensis - Liu, Zhixiang; Huang, Tingting; Shi, Qing; Deng, Zixin; Lin, Shuangjun (Frontiers in Microbiology, 2023)
Enterobactin is an archetypical catecholate siderophore that plays a key role in the acquisition of ferric iron by microorganisms. Catechol moieties have been shown to be promising siderophore cores. Variants of the conserved 2,3-dihydroxybenzoate (DHB) moiety with structural modifications expand the bioactivity. Streptomyces are characterized by metabolites with diverse structures. The genomic sequence of Streptomyces varsoviensis indicated that it possessed a biosynthetic gene cluster for DHB containing siderophores and metabolic profiling revealed metabolites correlated with catechol-type natural products. Here, we report the discovery of a series of catecholate siderophores produced by S. varsoviensis and a scale-up fermentation was performed to purify these compounds for structural elucidation. A biosynthetic route for the catecholate siderophores is also proposed. These new structural features enrich the structural diversity of the enterobactin family compounds. One of the new linear enterobactin congeners shows moderate activity against a food-borne pathogen Listeria monocytogenes. This work demonstrated that changing culture conditions is still a promising approach to explore unexplored chemical diversity. The availability of the biosynthetic machinery will enrich the genetic toolbox of catechol siderophores and facilitate such engineering efforts.